Evaluasi Pembiayaan Pembangunan Infrastruktur Pedesaan - Gunarto, Danang; ., Trimawan (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2022)
Volume estimation and the financial project are essential as technical calculations. This research is to study urban project finances held without proper planning, and the research sample is nine urban. The research method compares the budget available and the estimation calculation based on field observation according to field observation. Unit price analysis use SNI (Standart Nasional Indonesia) method. From the analysis results, the calculated cost and budget ceiling are different. According to field observation, the average budget ceiling is Rp 116,000,000.00, higher than the computed cost of Rp 105,900,000.00. However, according to field observation, the standard deviation of estimation calculation is Rp 46,400,000.00, and the budget is Rp 15,700,000.00. This matter shows that the quality of urban infrastructure projects is varied.